Reasoning strategies, dispositions and identity in critical reading-thinking - Mohamad Ali, Afiza (IIUM Press, International Islamic University Malaysia, 2017)
This book presents an investigation into second language students’ reasoning processing strategies in taking critical reading-thinking tests, and their skills and dispositions, as well as their perceptions regarding critical reading-thinking. The term ‘critical reading-thinking’ is coined as the research focuses on students’ critical reading and critical thinking is an inextricable part of this. It investigates students’ critical reading and critical thinking skills and dispositions. The study is set against a background of recent research into critical thinking and reading comprehension in a second language. Two introspective methods were used: interviews and think alouds. The data was transcribed and coded for identification of reasoning strategies, dispositions and understanding in respect to critical reading-thinking. A case study revealed that the difference in strategy use between the L1 and L2 critical reading test questions that were supposed to test the same skill was influenced by the nature of the questions, and that the questions ‘tested’ for different capabilities in strategy use, not the same ‘skill’ as is claimed. The majority strategies indicated that inference acted as an over-arching strategy that linked to the reasoning strategies which made inferences from contextual clues, background knowledge and knowledge of formal schemata. Students’ critical reading-thinking dispositions and their understanding and awareness of the importance of critical reading-thinking as part of the identity of a university student are also discussed. Some implications of the findings for pedagogy and for future research into critical reading in a second language are explained.